PENGARUH PROMOSI, HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN SALON SHERYL - Trianto, Feren Ebrik; Azhad, Muhammad Naely; Hermawan, Haris (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This research is motivated by an increase and a decrease, Salon Sheryl experienced a decline in 2020 - 2021 due to a pandemic. in this study that Salon Sheril is in the midst of an increasingly fierce competition phenomenon. Theepurposeeoffwritinggthissthesississtoo determine consumer satisfaction and marketing strategy by forming loyal customers to increase the wider market through promotion, price and service quality. This type of research is quantitative is a type of research that uses measurements and numbers. Theepopulationnin thissstudyyareepeopleewhoouse the services of Salon Sheryl. Theesampleeused was 70 people with purposive sampling technique, the analysis tool useddmultipleelinearrregression. The resultssshoweddthattpromotionnanddprice had aasignificantteffect on consumer satisfaction while service quality had no significant effect on customer satisfaction.